Moving Beyond Trauma: Activating Resilience to Support Our Most Vulnerable Youth - JoAnne Malloy; Sara Manisco Chapo; Kathryn Francoeur (International Journal of School Social Work, 2023)
It is well-documented that exposure to toxic stress in childhood can contribute to impaired social, emotional, behavioral, and neuro-biological development that often results in learning difficulties, poor emotional regulation, an inability to develop healthy relationships, and impaired problem-solving skills. Further, youth who grow up in unsafe environments or are subjected to structural inequality are faced with challenges over which they have no control. Using a positive, future-oriented, and trauma-responsive perspective while intentionally building resilience can effectively engage and support youth to overcome feelings of hopelessness and achieve positive outcomes. This paper includes a qualitative study of protective factors as identified by youth who participated in an intervention designed to support them to articulate, develop, and pursue their goals for transition from adolescence to adulthood. The paper includes a description of how a youth-driven planning and social support intervention can build resilience and promote a positive, future orientation. The study also emphasizes the need for further research about the impact of relationship-based, person-centered approaches on building resilience and improved outcomes for youth and young adults who have experienced significant trauma.
Keywords: Trauma; resilience; wraparound; RENEW; teacher-student relationships; school mental health; school social work.